Descripción de Sectiliclava placidae sp. nov. (Hymenoptera: Encyrtidae) de México, con la clave para especies del Género - Monrreal Hernández, Laura S.; Trjapitzin, Vladimir A.; Ruíz Cancino, Enrique (Instituto de Ecología, A.C., 2001)
In this paper, Sectiliclava placidae sp. nov. is described, and the fore wing and antenna are illustrated from specimens collected with entomological net in Ciudad Victoria, Tamaulipas, México. Information about distribution is included. A key to species of the genus is presented.